GLICEMIA EN AYUNAS Y PRONOSTICO OBSTRETICO-PERINATAL: UNA NUEVA CONSIDERACION - Pacora Portella, Percy (2024)
Blood samples in the rasting state were drawn rrom 1,560 non diabetic Peruvan pregnant women at 26 to 36 weeks or gestatlon in order to establish a normal range für fasting serum glucose in pregnancy (ortho-tolouidine method) and to examine whether maternal-fetal prognosis differs when maternal fasting blood sugar (FBS) values are beyond this range. The 3rd, 50th and 95th percentiles were SO, 67, 80 and 85 mg/dl, respectively. Pregnant women with diabetes risk factors had mean serum glucose values higher titan pregnant women without such risk factors significantly. Follow up was completed on 1,415 (90.7%) of the pregnancies and 1,043 (67%) of the newborns. Maternal FDS showed a positive association to diabetes rlsk factors, pregnancy complicatlons, feto-pelvic disproportion, shoulder dystocia, operative deliveries and perinatal morbidity and mortality. A significant increase In the maternal-fetal prognosis occurred when maternal FDS was beyond the range SO • 79 mg/dl (2.8 • 4.4 mmol/L). Maternal FDS values should be considered a reUable index at predicting maternal and perinatal outcome.